2003
DOI: 10.1242/jcs.00228
|View full text |Cite
|
Sign up to set email alerts
|

Differential usage of two in-frame translational start codons regulates subcellular localization ofArabidopsis thalianaTHI1

Abstract: Arabidopsis thaliana THI1 is encoded by a single nuclear gene and directed simultaneously to mitochondria and chloroplasts from a single major transcript. In vitro transcription/translation experiments revealed the presence of two translational products by the differential usage of two in-frame translational start codons. The coupling site-specific mutations on the THI1 encoding sequence with green fluorescent protein (GFP) gene fusions showed that translation initiation at the first AUG directs translocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 40 publications
1
46
0
3
Order By: Relevance
“…The shorter isoform may be targeted to mitochondria, while the longer isoform tends to be targeted to the plastid. The alternative upstream initiation site can even take the form of a non-AUG start codon, or it may be an AUG in a weak context (Kobayashi et al, 2001;Kobayashi et al, 2002;Chabregas et al, 2003;Silva-Filho, 2003;Christensen et al, 2005;Wamboldt et al, 2009). Two related cases deserve special attention.…”
Section: Alternative Translation Initiation Sitesmentioning
confidence: 99%
“…The shorter isoform may be targeted to mitochondria, while the longer isoform tends to be targeted to the plastid. The alternative upstream initiation site can even take the form of a non-AUG start codon, or it may be an AUG in a weak context (Kobayashi et al, 2001;Kobayashi et al, 2002;Chabregas et al, 2003;Silva-Filho, 2003;Christensen et al, 2005;Wamboldt et al, 2009). Two related cases deserve special attention.…”
Section: Alternative Translation Initiation Sitesmentioning
confidence: 99%
“…Arabidopsis THI1 localizes to the mitochondria and chloroplasts (Chabregas et al, 2003). Previously, Belanger et al (1995) used a THI1 antibody to show that the maize THI1 protein localizes to plastids.…”
Section: Thi2 Is a Plastid-localized Proteinmentioning
confidence: 99%
“…Further characterization showed that THI1 has two functions: it is involved in the thiazole synthesis of the thiamine biosynthesis pathway and in DNA repair [28,29]. Also, THI1 possesses a signal peptide at its N terminus, which targets the THI1 protein to mitochondria and chloroplasts [31,32]. The second is the Arabidopsis thaliana HMPPK/TMPPase gene (At1g22940) [30,33].…”
Section: Introductionmentioning
confidence: 99%